Recent insights into chemical and pharmacological studies of bee bread - Khalifa, Shaden Ali M.; Elashal, Mohamed; Kieliszek, Marek; Ghazala, Naglaa E.; Farag, Mohamed Ali; Saeed, Aamer; Xiao, Jianbo; Zou, Xiaobo; Khatib, Alfi; Göransson, Ulf; El-Seedi, Hesham R. (Elsevier Ltd, 2020)
Background: Bee bread is a product of the fermentation of a mixture of pollen, nectar and bee saliva that is inoculated by a wide range of bacteria and yeasts necessary for fermentation after storage in comb cells. Bee bread is regarded as the chief protein resource that bees can utilize, especially for feeding of larvae and adults. Since ancient times, bee bread has been used in different cultures for several nutritional and therapeutic purposes.